(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In the absence of a standardized tool that measures the Mathematical reflective thinking of Filipino Senior High School (SHS) learners in meeting the requirements of 21st century learning, this study proposes a scale which covers the entire problem-solving process, self-reflection, mastery, feedback, and realization. These factors indicate areas on how reflection is activated based on students’ actions. This study is helpful in measuring and controlling the degree of possessing the reflective thinking skill and in the subject of planning research studies for development. This Mathematical Reflective Thinking Scale (MRTC) assists the teachers in determining on which step of the problem solving do their students experience difficulty on, what type of reflective habits they have and evaluating within the framework of scale dimensions, whether or not students possess any self-reflection, mastery, reasoning, questioning, evaluation, realization, and feedback habits and in designing instructional strategies. Objectives: The study analyses the psychometric properties of the MRTC for Filipino SHS students employing the Rasch Model to provide a baseline reference in prescribing standardized tools in meeting 21st century learning. Methods: The study employed descriptive-survey using the partial-credit Rasch Model analysis to evaluate the reliability and validity of MRTS for Filipino SHS. The participants of the study were 768 students coming from 47 SHS from the three major islands of the Philippines which are Luzon, Visayas and Mindanao, and they were selected using stratified-random sampling. Results: Using a partial-credit Rasch modelling (Winsteps), the findings revealed that the new instrument was determined to be largely psychometrically sound, although two problematic items were also noted as reasons for further refinement. The study also evaluated the significance of several parameters as determined by the MRTS. items in contributing to students’ reflective thinking in dealing with Mathematics problem-solving. Conclusions: Finally, the proposed standardized tool is expected to contribute to the work of various stakeholders in Mathematics education in achieving quality basic education in the Philippines through the development of critical thinking and problem solving as reflective thinking skills to learners which facilitate reflective learning.